Balinese Cultural Diplomacy Through Culinary Products: A Study of Semiothic Communication - Suryawati, I Gusti Agung Alit (Universitas Telkom, 2024)
Besides having a wealth of arts and culture, Bali's cultural tourism potential is also in the form of traditional culinary products. What is the variety of traditional Balinese culinary? Why can traditional Balinese culinary products be used as an effective means of communication and Balinese cultural diplomacy? As a form of qualitative research, research data was collected through literature, observation and interviews with observers of Balinese culture. The collected data is then analyzed with the semiotic theory of communication. The results of the study show that traditional Balinese food and beverage culinary products are part of the archipelago's cuisine which are formulated from local agricultural ingredients, packaged and served in a distinctive way, and have tantalizing flavors so that they develop into culinary tourism objects favored by tourists. Apart from being the cultural identity of the Balinese people, traditional Balinese culinary products are also an effective means of communication and Balinese cultural diplomacy. People who enjoy traditional Balinese culinary dishes will be more familiar with Balinese traditions and culture. Traditional Balinese culinary tourism needs to be maintained and developed. Keywords: culinary products, Bali, cultural diplomacy